A Systematic Review of Architecture Stimulating Attention through the Six Senses of Humans - Chaniporn Thampanichwat; Pratsanee Meksrisawat; Narongrit Jinjantarawong; Somchok Sinnugool; Prima Phaibulputhipong; Pornteera Chunhajinda; Bhumin Bhutdhakomut (My University, 2024)
The climate change crisis is negatively impacting the mental health of people worldwide. Attention is a pivotal pathway to healing ourselves and the world, as it is a sensory process that enhances mental health and promotes sustainable behavior. Despite architecture’s potential to captivate all six human senses immediately, there is still a significant gap in research. Thus, this study aimed to identify architectural features that stimulate attention through the six human senses: visual, touch, auditory, olfaction, taste, and emotion. This review article was conducted by searching data from Scopus in February 2024, identifying 4844 related publications. After data screening following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, 32 relevant and accessible research works were identified. Finally, data were extracted from the selected articles and analyzed using thematic analysis to explore their relevance to all six senses. The results reveal that the architectural features predominantly eliciting attention are mainly related to visual sensory stimuli. Closely following are the architectural features perceived through the emotional sense. The architecture that promotes attention is minimally associated with touch, auditory, and olfaction senses. Lastly, no architectural features were found to influence attention perceived through the sense of taste. Nevertheless, this study merely synthesizes data from previous research studies. Future research endeavors should validate this study’s findings for broader implications empirically.
Keywords: Relevance; Thematic Analysis; Color perception and design